The Challenges in Adoption of Transparency in Block Chain Technology in Logistics of Food Supply Chain - Yousuf, Aqsa (Journal of Applied Research and Multidisciplinary Studies, 2022)
Block chain ledger technology is one of the key emerging models to be adopted by business if they want to survive in the upcoming competitive environment. It is necessary for food supply chain to overcome challenges like quality control, food frauds, maintenance, traceable and clean operation, customer satisfaction, digitization requirements and any other, this is only possible by implementation of block chain technology, which is still in earlier stages having a lot of potential for managing such challenges. This paper also discusses different challenges and risk associated with food supply chain while implementing block chain technology, discussed by many other researchers as well. In the end this paper discusses, recommends and highlights those areas where more research can be done.